2021
DOI: 10.48550/arxiv.2107.03945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Abelian Electric Field Correlator at NLO for Dark Matter Relic Abundance and Quarkonium Transport

Tobias Binder,
Kyohei Mukaida,
Bruno Scheihing-Hitschfeld
et al.

Abstract: We perform a complete next-to-leading order calculation of the non-Abelian electric field correlator in a SU(N c ) plasma, which encodes properties of the plasma relevant for heavy particle bound state formation and dissociation. The calculation is carried out in the real-time formalism of thermal field theory and includes both vacuum and finite temperature contributions. By working in the R ξ gauge, we explicitly show the results are gauge independent, infrared and collinear safe. The previous results on the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…I reviewed recent progress in applying the open quantum system framework to study quarkonium dynamics inside the QGP, with a focus on the QGP correlators of the chromoelectric fields that enter the Lindblad equations in both the quantum Brownian motion and the quantum optical limits. The same framework has also been applied to study Dark Matter bound state formation in the coannihilation scenario in the early universe [26]. Some problems of jet quenching in heavy ion collisions have also been studied in the open quantum system framework [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I reviewed recent progress in applying the open quantum system framework to study quarkonium dynamics inside the QGP, with a focus on the QGP correlators of the chromoelectric fields that enter the Lindblad equations in both the quantum Brownian motion and the quantum optical limits. The same framework has also been applied to study Dark Matter bound state formation in the coannihilation scenario in the early universe [26]. Some problems of jet quenching in heavy ion collisions have also been studied in the open quantum system framework [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In the dynamics of open heavy quarks, the heavy quark carries color all the way, so the Wilson lines extend to both positive and negative infinite times. Perturbative calculations [26,29] showed that these two correlators agree in the temperature dependent part but differ by a finite constant at next-to-leading order. See also the discussions in Ref.…”
Section: Chromoelectric Field Correlators Of Qgpmentioning
confidence: 96%
See 1 more Smart Citation
“…This does not only make the mediator long-lived compared to the Hubble time around the cosmological production of χ but also implies a long lifetime in the lab today. The expected decay length in the lab is given by ∆x Γ t βγc (22) where γ is the Lorentz factor and β the velocity of the decaying particle in natural units. We have checked that for the values of λ χ preferred by freeze-in and with a realistic distribution of γ factors ∆x ≥ 100 m throughout the considered parameter space.…”
Section: B Cosmological and Laboratory Constraintsmentioning
confidence: 99%
“…However, aside from the abundant production at colliders, the SM gauge interactions also give rise to large non-perturbative corrections to the annihilation rates of the mediators in the early Universe. While these effects have been investigated in DM freezeout before [16][17][18][19][20][21][22][23], they have not been considered in the context of non-thermal production and it is not clear how large their impact on the cosmologically preferred parameter space is.…”
Section: Introductionmentioning
confidence: 99%